1998
DOI: 10.1200/jco.1998.16.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation that chromosome 18q allelic loss in colon cancer is a prognostic indicator.

Abstract: Chromosome 18q allelic loss is a prognostic marker in colorectal cancers. Chromosome 18 LOH studies may be useful in identifying patients with stage II disease who are at high risk for recurrence, and as such might benefit from adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(75 citation statements)
references
References 18 publications
3
70
0
2
Order By: Relevance
“…Loss of heterozygosity (LOH) is one of the major types of genetic inactivation, and the long arm of chromosome 18 is the most frequently deleted region in colorectal cancers. To date, many reports suggest that this deletion is a molecular predictor that affects survival (Fearon et al, 1990;Jen et al, 1994;Chung, 1998;Lanza et al, 1998;Ogunbiyi et al, 1998;Jernvall et al, 1999;McLeod and Murray, 1999;Sarli et al, 2004). We too reported that the allelic deletion of chromosome 18q was associated with poorer prognosis in stage III colon cancer after adjuvant chemotherapy (Watanabe et al, 2001.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Loss of heterozygosity (LOH) is one of the major types of genetic inactivation, and the long arm of chromosome 18 is the most frequently deleted region in colorectal cancers. To date, many reports suggest that this deletion is a molecular predictor that affects survival (Fearon et al, 1990;Jen et al, 1994;Chung, 1998;Lanza et al, 1998;Ogunbiyi et al, 1998;Jernvall et al, 1999;McLeod and Murray, 1999;Sarli et al, 2004). We too reported that the allelic deletion of chromosome 18q was associated with poorer prognosis in stage III colon cancer after adjuvant chemotherapy (Watanabe et al, 2001.…”
mentioning
confidence: 77%
“…A study by Lanza et al (1998) also showed similar results in that patients with stage II disease whose tumour had no 18q allelic loss demonstrated a 5-year survival rate of 96%, while those with stage II disease and 18q allelic loss showed a 5-year survival rate of only 54%. Ogunbiyi et al (1998) reported that Chromosome 18q allelic loss was significantly associated with reduced disease-free and disease-specific survival in patients with stage II (P ¼ 0.05 and P ¼ 0.0156) and III disease (P ¼ 0.038 and P ¼ 0.032). We showed that microsatellite stable (MSS) patients with stage III colorectal cancer showed poor prognosis when chromosome 18q showed allelic loss (P ¼ 0.006) (Watanabe et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In multiple regression proportional hazards models, 18q was an independent prognostic marker and 18q loss gave a 2.5 to 3.0-fold higher risk of death. The prognostic importance of 18q allelic loss was verified in a study of 126 patients (stage I, 32; II, 50; III, 44), using four microsatellite markers on microdissected tumour (Ogunbiyi et al, 1998). Loss of 18q was an independent marker of poor prognosis, with a 1.65 relative risk of disease-free survival.…”
Section: Deleted In Colon Cancer/allelic Variance At 18qmentioning
confidence: 99%
“…More interesting in this context is the fact that both, APC (chromosome 5q) and RP1 are located within chromosomal regions known to be lost or altered in a high percentage of colorectal cancers, too. The localization of the RP1 gene on chromosome 18q21 links RP1 to a region that is a ected in up to 50% of all patients with colorectal cancer (Ogunbiyi et al, 1998). The 18q chromosomal region is frequently altered either by a complete loss of the long arm or by deletions in the q21-23 region.…”
Section: Discussionmentioning
confidence: 99%